An assessment of internal controls in budget hotels in Malaysia - Chang, Su Juen; Mustapha, Mazlina (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Prior studies claim that having effective internal controls creates a competitive advantage, as organizations with effective internal controls will be able to take on additional risk, especially if the services offered are very similar. It is also claimed that having internal controls in place, would lead the organization to have a more effective and efficient operations, enabling them to provide a more reliable financial reporting and create better compliance with law and regulation. Among the industries which offer similar services is the hotel industry. This study attempts to examine the impact of internal controls practices in budget hotels in Malaysia on their performance. The internal controls components outlined by COSO are used to examine the relationship between the variables. Questionnaires were sent to 100 budget hotels in Kuala Lumpur and Selangor; however, only 32 questionnaires were returned and usable for the purpose of the study. Multiple regression analysis was employed to analyze the data. The findings reveal that control environment, risk assessment and information and communication are significantly related to the performance of the budget hotels in the study. This research contributes to a better understanding of internal control in the budget hotels and provides information to the management of these hotels on the importance of internal control in their daily operations, as well as to remain competitive.